ANALISIS STRATEGI PENGEMBANGAN PRODUK TABUNGAN AL-QASHWA HAJI PADA PT BPRS JAM GADANG (PERSERODA) BUKITTINGGI - Nur Hikmah; Zulhelmi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research is motivated by the low customer interest in Hajj al- qashwa savings products and the number of customers who always fluctuate in 2019 and 2021, and also the number of customers who withdraw before the disbursement is made. The formulation of the problem in this research is how the hajj al-qashwa savings product development strategy is in increasing the number of customers at PT. BPRS Jam Gadang Perseroda Bukittinggi. The purpose of the research is to find out the product development strategy of Hajj al- qashwa savings in increasing the number of customers at PT BPRS Jam Gadang Perseroda Bukittinggi. The type of research used in this research is field research using qualitative methods. The data sources used are primary data and secondary data, with data analysis techniques used, namely, data collection, data processing, data presentation, conclusion verification. Based on the results of the study it can be concluded that the product development strategy of Hajj savings al- qashwa at PT. BPRS Jam Gadang Perseroda Bukittinggi is by introducing products to customers by means of socialization and distribution of brochures, innovating products, expanding marketing, and imitating competitor strategies used in its product development strategy.